Digital Financial Instruments, Financial Inclusion, and Regional Economic Performance in Indonesia - Puspita, Maylawati Arum; Oktavilia, Shanty (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study examines the joint effects of digital financial instruments and financial inclusion indicators on regional economic performance during the post-pandemic period of accelerated digital transformation. Research Objectives: The study aims to analyze the impact of electronic money transactions, third-party funds of Rural Banks (BPR), credit card transactions, and household internet access on Gross Regional Domestic Product (GRDP) per capita. Research Methods: Using panel data from 38 provinces over the 2020–2024 period, this study employs panel regression analysis. Based on the Chow and Hausman tests, the Fixed Effects Model (FEM) is selected as the most appropriate estimator. Empirical Results: The findings indicate that electronic money transactions, credit card transactions, and household internet access have a positive effect on GRDP per capita. In contrast, third-party funds of Rural Banks do not demonstrate a significant relationship with regional economic performance. Implications: The results underscore the importance of strengthening digital financial ecosystems and expanding digital infrastructure to foster inclusive and sustainable regional economic growth in emerging economies. JEL Classification: O16, O33, R11, G21